STRATEGI STASIUN TV9 LOMBOK DI ERA DISRUPSI - dkk, Sahril Halim (KOMUNIKE, 2018)
Disruption era is a period that requires television broadcasters to do media innovation and creativity to keep up with the times and technology. The tight competition in the broadcasting industry requires that media companies are able to survive in the face of competitors. This paper aims to analyze the strategies used by TV9 Lombok, so that still exist in the media competition is intense. Innovation and creativity against the content of the news and entertainment media, as well as the application of divergence be a strategy used by TV9 Lombok to stay aﬂoat. The methods used in this research is qualitative interpretive approach to address the strategies implemented by TV9 Lombok. Results of the study that the application of divergence by TV9 Lombok is to respond to changes in the way the audience in watching television broadcasts that were previously conventionally, but now the public can enjoy the content of television broadcasts online. The concept of this divergence is applied as the effort’s effectiveness in promoting the TV9 broadcasts by utilizing streaming youtube, social media to web news portals to closer to their audience. So do TV9 Lombok as efforts in maintaining its existence in the world of broadcasting